Blue Light Fluorescence in Marine Sediments - Emily Carter Jones; Kelsey A. Williams; Ervan G. Garrison; Paul A. Schroeder (Geosciences, 2025)
Mineral fluorescence under different portions of the visible and invisible light spectrum has a long history of scientific study. In our study of marine sediments from the Georgia Bight, we have utilized the blue portion of the light spectrum in the 445 nanometer (nm) range. The use of fluorescence has proven very useful in microscopic analyses of carbonate minerals. While the sediment prism of the inner-to-mid continental shelf in the southeastern Atlantic is predominantly siliceous, the dissolution and deterioration of marine shell contribute a significant amount to the fabric of any sediment sample. Together with carbonate minerals such as dolomite, eroded from basement rock and redeposited on the shelf, a potentially robust fluorescent response was expected and observed in samples. In marine sediments, blue light illumination has produced an easily observed fluorescent response in both underwater and in laboratory settings. This fluorescence can be attributed to carbonate minerals—calcite/aragonite. Feldspars are major accessory minerals in the sediment prism of the Georgia Bight, and much of the observed fluorescence in our samples can be attributed to their presence. To identify specific minerals responsible for any observed fluorescence, X-ray diffraction and energy dispersive spectroscopy were utilized. This combined methodology of luminescent excitation, X-ray diffractometry and spectroscopy has produced the results reported herein.